RELEVANSI PEMIKIRAN PENDIDIKAN ISLAM MUHAMMAD IQBAL TERHADAP TANTANGAN PENDIDIKAN MODERN : Biography of Muhammad Iqbal, Works of Muhammad Iqbal, Relevance of Muhammad Iqbal's Islamic Educational Thoughts to the Challenges of Modern Education - aini, risma sulistia (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2025)
This study aims to analyze the relevance of Muhammad Iqbal's Islamic educational thoughts in facing the challenges of education in the modern era. Iqbal's thoughts that integrate the concepts of khudi (self), freedom of thought, and actualization of human potential, make an important contribution to the formation of individuals who are not only intellectually intelligent, but also have high character, creativity, and social awareness. In the midst of the development of globalization and technological advances, Islamic education faces various challenges, including mental colonization, dogmatism, and limitations of thought. In this context, Iqbal's thoughts on freedom and creativity in education become relevant as a solution to free Muslims from the shackles of limited thinking and encourage them to develop their potential to the maximum. This study uses a literature review method by collecting various literature related to Iqbal's thoughts and their application in Islamic education. The results of the study show that Iqbal's concepts can provide a new direction in developing Islamic education that is more inclusive, innovative, and responsive to the challenges of the times. Therefore, Iqbal's educational thoughts are very relevant to be implemented in the Islamic education system in the current era of globalization.